Effects of speed of ration step-up and monensin on ruminal pH, lactate, and protozoal population in feedlot cattle - Towne, G.; Brandt, Robert T., Jr.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fluctuations in ruminal pH, lactate concentration, and ciliated protozoal population were monitored in 40 individually fed crossbred heifers that were stepped up to an 85% concentrate diet either slowly (12 d) or rapidly (3 d), with or without monensin (30 ppm). Speed of step-up affected ruminal pH, lactate concentration and protozoal population initially (up to 28 d), but thereafter no differences occurred between the groups, suggesting adaptation to ruminal conditions. Monensin had no effect on ruminal pH, lactate concentration, or protozoal population.
Keywords: Beef; Ruminal microorganisms; Step-up Monensin; Feedlot cattle